Definition, Role, and Functions of Soil Related to the Knowledge Society and the Someș-Tisa Hydrographic Area (Romania) - Cioruța, Bogdan-Vasile; Coman, Mirela (Sustainability, 2022)
In Romania, under the aegis of the knowledge society, we naturally wondered if the soil still had a role, through the functions it fulfills, at the level of local communities. In this context, we set out, starting from the definition of soil as a cosmic–telluric–biotic product with notable valences in the transition of communities from hunting to knowledge-based societies, to make some scientific observations on the importance of soil resources. The research methodology was outlined around the importance and functions of soil in society by presenting the current state of land use in the Someș-Tisa region. As reference points, graphs on the hydrometeorological conditions made using the MeteoBlue application and an archive of the meteorological station in Baia Mare were used, as provided (per an open-access regime) by the Someș-Tisa Water Basin Administration and the Maramures County Council, respectively. Moreover, the research was completed with studies conducted by specialists, most of which were included in the Application Guide of the XVIII National Conference of Pedology held in 2006 in Cluj-Napoca. The research results showed that soil resources were still of vital importance for the communities in the Someș-Tisa area, where agricultural and agrotourism practices predominate. At the same time, it was noticed that the soil resources required increased attention as a result of the pollution resulting from the development of mining activities in large areas. Consequently, the soil resources in the Someș-Tisa area, which closely define the evolution of local communities, should be carefully monitored and subject to good practice guidelines specific to the objectives of sustainable development.